Enhancing Cookery Skills Through Contextualized Instruction Using Locally Available Resources - Dantes, Mary Grace (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between learners’ cookery skills and the implementation of contextualized instruction using locally available resources in Technology and Livelihood Education (TLE). Grounded in the concept of contextualized learning, the research emphasized aligning instruction with students’ local environment, culture, and available materials to enhance practical competencies. A descriptive-correlational research design was employed, involving Grade 10 cookery students as respondents. Data were gathered using structured instruments assessing cookery skills, the level of contextualization in instruction, and challenges encountered, and were analyzed using descriptive statistics and Pearson r correlation. Findings revealed that students demonstrated a satisfactory level of mastery in cookery skills, particularly in basic food preparation, sanitation, and safety practices, although improvement is needed in advanced techniques and presentation. Learners also exhibited a satisfactory level of contextualization, especially in integrating local ingredients and adapting recipes to cultural practices, though the use of indigenous tools and broader community engagement remained limited. The study further identified moderate challenges, including seasonal availability of ingredients, limited budget, restricted access to traditional tools, and difficulty adapting foreign recipes to local contexts. Importantly, results showed a statistically significant moderate positive relationship (r = 0.687) between learners’ cookery skills and the implementation of contextualized instruction, indicating that the use of locally available resources enhances skill development. The study concludes that contextualized instruction is an effective approach for improving cookery competencies and recommends increased integration of local resources, hands-on training, and support for traditional culinary practices. This research aligns with Sustainable Development Goal 4 (Quality Education) by promoting relevant and inclusive learning, and SDG 12 (Responsible Consumption and Production) through the use of local and sustainable food resources. The sustainability impact of the study lies in strengthening culturally responsive education, promoting local food systems, and supporting community-based and resource-efficient learning practices.
Keywords: Contextualized instruction; Cookery skills; Local resources; Sustainability; Technology and Livelihood Education